1996
DOI: 10.1021/bi960869n
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Secondary Structure and Conformation of Puroindolines by Infrared and Raman Spectroscopy

Abstract: The conformation of puroindoline-a and -b, two basic lipid-binding proteins isolated from wheat seedlings, has been studied for the first time by infrared and Raman spectroscopy. The infrared results show that puroindoline-a and -b have similar secondary structure composed of approximately 30% R-helices, 30% -sheets, and 40% unordered structure at pH 7. The conformation of both puroindolines is significantly pH-dependent. The reduction of the disulfide bridges leads to a decrease of the solubility of puroindol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 52 publications
5
71
1
1
Order By: Relevance
“…Puroindoline proteins possess a characteristic tryptophan-rich domain and cysteine backbone; isoforms occur in the starchy endosperm of the Triticeae. Their secondary structure, determined by infrared and Raman spectroscopies, is comprised of approximately 30% -helices, 30% -sheets, and 40% unordered structure at pH 7.4 in solution (Bihan et al 1996). Puroindoline genes are present throughout the Triticeae tribe of the Poaceae (Gramineae), including wheat (Triticum sp.…”
Section: Introductionmentioning
confidence: 99%
“…Puroindoline proteins possess a characteristic tryptophan-rich domain and cysteine backbone; isoforms occur in the starchy endosperm of the Triticeae. Their secondary structure, determined by infrared and Raman spectroscopies, is comprised of approximately 30% -helices, 30% -sheets, and 40% unordered structure at pH 7.4 in solution (Bihan et al 1996). Puroindoline genes are present throughout the Triticeae tribe of the Poaceae (Gramineae), including wheat (Triticum sp.…”
Section: Introductionmentioning
confidence: 99%
“…proteins are able to bind to polar phospholipids, increasing the permeability of model membranes (10,11,34,35) as observed for the Trp-rich antimicrobial peptides indolicidin and tritrpticin (5,9).…”
Section: Discussionmentioning
confidence: 97%
“…The function of puroindolines in vivo is still unknown, but their in vitro antifungal and antibacterial activities together with the localization of the proteins in the aleurone of the seeds suggest that they play an important role in the protection of the seed (11,35). Structural studies revealed that puroindolines and Ace-AMP1 present tryptophan residues that are exposed to the solvent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the technique permits to determine the conformation of a non-specific wheat phospholipid transfer protein, and to study the role of disulphide bridges in the stabilization of the α-helical structure. In addition, Raman microspectroscopy was used to determine the secondary structure and conformation of puroindolines, lipid-binding protein of wheat [64].…”
Section: Raman Spectroscopymentioning
confidence: 99%